An efficient outsourced attribute-based encryption scheme in the device-to-device mobile network - Huawei Wang; Ye Li; Yingnan Jiao; Zhengping Jin (International Journal of Distributed Sensor Networks, 2019)
Device-to-device communication is considered as one of the hopeful technologies for proximal communication, which plays a vital role in the wireless systems and 5G cellular networks. The outsourced attribute-based encryption scheme is convinced to be very suitable for secure device-to-device communication since it allows not only fine-grained sharing of encrypted data but also achieves high efficiency in the decryption of general attribute-based encryption schemes. However, almost all existing outsourced attribute-based encryption schemes can hardly be applied directly in the device-to-device communication because many heavy computation operations, such as pairing and modular exponentiations, cannot be taken on the mobile devices in the device-to-device network. In this article, we propose a concept of outsourcing threshold decryption for attribute-based encryption and design a new efficient outsourcing threshold decryption scheme for ciphertext-policy attribute-based encryption. In our definition of outsourcing threshold decryption, the decryption, which is a computationally expensive operation, is outsourced to multiple semi-trusted and lightweight computing devices determined by an access structure and can be jointly taken by these devices. Our scheme supports proxy re-encryption which enables the decryption delegation. Finally, security and efficiency analyses of our proposed method indicate that our proposal guarantees strong security against chosen plaintext attacks and requires less outsourced computation and communication cost than the existing outsourced attribute-based encryption schemes.